(untitled) (Veterinary Science, 2017)
Inactivated vaccines of national production, for use in the equine, carried mostly in its formulation as an adjuvant, aluminum hydroxide Al(OH)3. Nowadays there are new adjuvants potentially superior to the traditional, either with respect to an increase in the time of permanence of the antigen in the host, and the immune response that induce. In the present work was compared the action of adjuvant Emulsigen respect aluminum hydroxide, which were used in a vaccine against equine influenza. For this purpose were established two test models, horses and guinea pigs, and the immune response induced was assessed by means of the determination of antibody titers. The results showed higher titers and extended serum antibodies persistence with the vaccine adjuvanted with Emulsigen, in relation to that adjuvanted with Al(OH)3, likewise were not observed adverse reaction in the site of inoculation.